Self-Leadership: Toward an Expanded Theory of Self-Influence Processes in Organizations - Manz, Charles C. (Academy of Management Review, 1986)
The considerable attention devoted to individual self-influence processes in organizations has been limited to scope, focusing primarily on self-management that facilitates behaviors that are not naturally motivating and that meet externally anchored standards. In this paper, individual self-control systems are viewed as the central control mechanisms within organizations. An expanded “self-leadership” view is developed that includes (a) self-imposed strategies for managing performance of tasks of low intrinsic motivational potential and (b) self-influence that capitalizes on the “natural”/intrinsic motivational value of task activity. Implications for theory and practice are addressed.